1996
DOI: 10.1016/s0022-5223(96)70459-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pulsatile and nonpulsatile systemic perfusion on renal sympathetic nerve activity in anesthetized dogs

Abstract: It is still controversial whether to pulse or not to pulse for the establishment of ideal extracorporeal circulation. We directly measured the renal sympathetic nerve activity in mongrel dogs (n = 10, weighing from 13 to 21 kg) to determine the effects of pulsatile and nonpulsatile systemic perfusion on the control of the sympathetic nerve activity during left ventricular assistance. Pulsatile perfusion was generated with an air-driven, diaphragm-type blood pump, and nonpulsatile perfusion was generated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 19 publications
1
43
1
Order By: Relevance
“…In previous studies the urine output value is used as an indicator for renal function -this has been shown to be the case by Urzua et al [25] and Badner et al [26] who reported a direct relationship of both urine output and glomerular fi ltration rate with systemic perfusion pressure. This may also explain the failure of urine output during cardiopulmonary bypass to predict postoperative renal function [27]. Colloid transfusion and urine output are shown in fi gure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies the urine output value is used as an indicator for renal function -this has been shown to be the case by Urzua et al [25] and Badner et al [26] who reported a direct relationship of both urine output and glomerular fi ltration rate with systemic perfusion pressure. This may also explain the failure of urine output during cardiopulmonary bypass to predict postoperative renal function [27]. Colloid transfusion and urine output are shown in fi gure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Already in 1972 Calne et al [34] described a squirt liver perfusion of porcine liver and showed superior results when the perfusate was administered intermittently at higher pressures as a squirt of a bolus of perfusate. Studies of kidney preservation also suggested better organ function and microcirculation by using a pulsatile rather than a nonpulsatile perfusion technique [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CPB patients have a higher risk of stroke (5,6). There are many possible reasons for those phenomena, such as embolism (7,8) caused by the cannula jet hitting the aortic wall (9)(10)(11), or manipulation of the aorta by cannulae or clamps (12)(13)(14). Different cannulae have been developed to improve the cerebral perfusion during CPB (15,16).…”
mentioning
confidence: 99%